Fossil fuels feed climate change and war: Time to quit them - Bößner, Stefan; Läderach, Peter R.D.; Johnson, Francis X; Kangogo, Daniel; Pacillo, Grazia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
The production, distribution, and consumption of fossil fuels are linked directly to climate change by driving up emissions, and indirectly related to conflict and human insecurity by benefitting a small number of often authoritarian countries. By relying on fossil fuels for energy security, the EU finds it difficult to wean itself off Russian gas, thus perpetuating a tense relationship with Moscow. But our dependency on fossil fuels also has negative consequences for the Global South, where climate change impacts are likely to be felt the hardest. While not without challenges, now is the time to “walk the walk” by following through with low carbon transitions. Overcoming these challenges is possible, but we must do it now. Neither the climate nor global peace and stability can wait.